Recueils manuscrits de chansons basques - Haritschelhar, Jean (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1988)
This article aims at highlighting the necessity of publishing the indexes of the handwritten song-books to be found in both public and private collections, since these indexes may be of use to researchers in the field of oral Basque literature. We present here the indexes of the famous song-book of Augustin Chaho, in the possession of Señora de Monzón, and of the song-book of Captain Duvoisin, which is in the library of the Basque Museum of Bayonne.